Bleach. 12, Flower on the precipice - Kubo, Tite (Kubo, Tite. Bleach (VIZ Media), 2006)
With reports of powerful intruders defeating a number of assistant captains, the inner sanctum of the Soul Society--the Seireitei, the home of the Soul Reapers--is put on a state of high alert.